Reading comprehension skills included in the content of the mathematics book for the sixth grade in the Syrian Arab Republic - سعود, هزار; نصور, رغداء (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current research aims to determine the reading comprehension skills included in the mathematics book for the sixth grade, and to know the availability of these skills in it. The researcher used the descriptive analytical method, and the study tools consisted of a content analysis tool, which included a list of reading comprehension skills, and the and the validity and reliability of the tools were verified, The research was implemented during the first semester of the academic year 2022\2021. The study sample included a mathematics book for the sixth grade with its six units, and the results of the research showed that the skill of interpretive comprehension came in the first place with a percentage of 68.57%, and the skill of literal comprehension came in the second place with a percentage of 20.57 %, while the skill of applied comprehension came in the last rank with a percentage of 10.85%. The research also presented several proposals, including: educating mathematics teachers about the importance of reading comprehension skills, guiding them towards using methods and activities, focusing on the learner’s activity through cooperative learning, problem solving, and projects, conducting studies to reveal the difficulties facing primary school students, which impede the development of understanding their readers, and work to consolidate and include applied comprehension skills in the mathematics book for the sixth grade